The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/jor.22222
|View full text |Cite
|
Sign up to set email alerts
|

Dose–response effect of an intra‐tendon application of recombinant human platelet‐derived growth factor‐BB (rhPDGF‐BB) in a rat Achilles tendinopathy model

Abstract: The purpose of this study was to assess whether intra-tendon delivery of recombinant human platelet-derived growth factor-BB (rhPDGF-BB) would improve Achilles tendon repair in a rat collagenase-induced tendinopathy model. Seven days following collagenase induction of tendinopathy, one of four intra-tendinous treatments was administered: (i) Vehicle control (sodium acetate buffer), (ii) 1.02 mg rhPDGF-BB, (iii) 10.2 mg rhPDGF-BB, or (iv) 102 mg rhPDGF-BB. Treated tendons were assessed for histopathological (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 37 publications
4
36
0
Order By: Relevance
“…Other concentrations have not shown a significant difference compared to the normal untreated control (Shah et al, 2013). On the other hand, ultimate tensile stress was only significantly higher, compared to the other groups, in the 1.02 μg of PDGF group.…”
Section: Single Bolus Injectionmentioning
confidence: 70%
See 4 more Smart Citations
“…Other concentrations have not shown a significant difference compared to the normal untreated control (Shah et al, 2013). On the other hand, ultimate tensile stress was only significantly higher, compared to the other groups, in the 1.02 μg of PDGF group.…”
Section: Single Bolus Injectionmentioning
confidence: 70%
“…From the literature covered in this review and the observations existing so far, it can be concluded that from the available delivery strategies, a single bolus injection of 10 µg of PDGF-BB one week post-operation (Shah et al, 2013) or a fibrin-based PDGF-BB delivery system loaded with much larger amounts than reported, e.g. 10 µg instead of only 0.5 µg (Thomopoulos et al, 2009), would probably be the most promising approaches.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations